The impact of consumer perceptions of product quality on green product purchase decisions: A cross-sectional study in Saudi Arabia - Alsiehemy, Ali Mohammed A (Edelweiss Applied Science and Technology, 2025)
This study explores the impact of consumer perceptions of product quality on green product purchasing decisions in Saudi Arabia. With growing environmental concerns, green consumerism has gained importance as customers increasingly shift towards eco-friendly alternatives. However, perceptions that green products are expensive or of lower quality often impede their acceptance. This research examines how quality perceptions, environmental awareness, and consumer preferences influence both purchase and repurchase intentions. A cross-sectional survey of 135 participants (52.6% male, 47.4% female) was conducted through an online questionnaire, and the data were analyzed using SPSS to assess the relationships between product quality perceptions, purchasing behavior, and demographic factors. The findings reveal that positive perceptions of product quality significantly enhance purchase intentions, while environmental considerations and personal preferences also play critical roles in decision-making. This study offers valuable insights for businesses and policymakers, helping them develop strategies to address consumer concerns and promote sustainable consumption, aligning with Saudi Arabia’s Vision 2030 goals.